2023
DOI: 10.1111/tan.15157
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies of response and side effects to the BNT162b2 vaccine in Italian healthcare workers: Increased antibody levels and side effects in carriers of the HLA‐A*03:01 allele

Abstract: The remarkable variability of response to vaccines against SARS‐CoV‐2 is apparent. The present study aims to estimate the extent to which the host genetic background contributes to this variability in terms of immune response and side effects following the administration of the BNT162b2 vaccine. We carried out a genome wide association study (GWAS) by genotyping 873 Italian healthcare workers who underwent anti‐SARS‐CoV‐2 vaccination with the BNT162b2 vaccine and for whom information about anti‐SARS‐CoV‐2 spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…This allele is present in one out of 10 individuals according to the frequencies obtained from the IBMDR and its frequency doubled in our cohort of strong responders. Two independent studies, both conducted on healthcare workers vaccinated with an mRNA vaccine, 8,9 found a significant correlation between HLA*03:01 and humoral response, similarly to ours. Despite some differences in analytical methods, sample selection and timepoints, their results appear consistent and confirm our previous finding of a lower HLA-A*03:01 frequency among weak responders.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This allele is present in one out of 10 individuals according to the frequencies obtained from the IBMDR and its frequency doubled in our cohort of strong responders. Two independent studies, both conducted on healthcare workers vaccinated with an mRNA vaccine, 8,9 found a significant correlation between HLA*03:01 and humoral response, similarly to ours. Despite some differences in analytical methods, sample selection and timepoints, their results appear consistent and confirm our previous finding of a lower HLA-A*03:01 frequency among weak responders.…”
Section: Discussionsupporting
confidence: 88%
“…It is perhaps not by chance that the three studies showing significant impact of HLA-A*03:01 on vaccine humoral response so far have been conducted on healthcare workers coming from the same geographical region. 8,9,11 The divergent results obtained with the UK study 21 may be explained by the different study population compared with ours, having thus different expected HLA allele frequencies. In addition, the use of an adenoviral vector-based vaccine in the study by Mentzel and coll.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the large sample study from the COVID-19 Host Genetics Initiative, only one human leukocyte antigen (HLA) class II allele, HLA-DRB1*04:01, has been found to confer a small decrease in the risk of critical COVID-19 (OR = 0.8) 2 . By contrast, we have documented a stronger association between HLA-A*03:01 and side effects following inoculation with the Pfizer-BioNTech COVID-19 mRNA vaccine 13 , which was subsequently replicated 14 .…”
Section: Introductionmentioning
confidence: 75%
“…13 INSERM UMR 1018, Paris, France. 14 INSERM Sponsor, Paris, France. 15 Centre d'Investigation Clinique, INSERM CIC 1403, Centre Hospitalo universitaire de Lille, Lille, France.…”
Section: Acknowledgementsmentioning
confidence: 99%